SUSTAINABLE CAREER OF MARRIED BALINESE WOMAN: THE EFFECT OF CAREER ADAPTABILITY AND WORK-LIFE BALANCE - Yani, Ni Wayan Merry Nirmala; Widya Hadi Saputra, I Gusti Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
In the last few decades, the role of women in the career world has undergone a significant shift. The aim of this research is to examine the influence of career adaptation on work-life balance, career adaptation on a sustainable career, and work-life balance on a sustainable career Balinese women who were married and decided to continue working. The number of samples used in this research was 155 samples. The data analysis technique used in this research is path analysis using SEM-PLS. The results of this research show that career adaptation has a significant positive effect on work-life balance, career adaptation has a significant positive effect on a sustainable career, and work-life balance has a significant positive effect on a sustainable career. This research strengthens career construction theory in solving the challenges faced by Balinese women in managing career adaptation, work-life balance, and sustainable careers.